The prevalence of undernutrition among students attending traditional Ethiopian orthodox Tewahedo church schools in northwest Ethiopia - Shiferaw, Yalelet Fentaw; Asmamaw, Desale Bihonegn; Engidaw, Melaku Tadege; Belay, Daniel Gashaneh; Birhan, Haileyesus; Negash, Wubshet Debebe (Frontiers in Public Health, 2023)
Background Undernutrition is a major public health concern affecting the health, growth, development, and academic performance of adolescents studying in school. During this crucial period, dietary patterns have a vital impact on lifetime nutritional status and health. The problem of undernutrition among particular groups of adolescents attending traditional schools has not previously been studied. Therefore, this study aimed to assess the prevalence of undernutrition and associated factors among adolescents aged 10–19 years attending Orthodox Church schools in northwest Ethiopia. Methods An institution-based, cross-sectional study design was employed, with data collected from March 1 to 30, 2021. A simple random sampling technique was used to recruit a total of 848 male attendees of traditional schools. Data were collected via an interviewer-administered semi-structured questionnaire. The nutritional status of participants was assessed using anthropometric measurements. The WHO Anthroplus software was used for analysis. Both bivariable and multivariable logistic regression analyses were conducted to identify the factors associated with nutritional status. The degree of association between the independent variables and the dependent variable was assessed using odds ratios, reported with 95% confidence intervals, and a threshold of p ≤ 0.05. Results The prevalence of undernutrition was found to be 61.3% [95% CI: 58.1, 64.6]. The likelihood of developing undernutrition was elevated among those adolescents who were following the traditional school levels of dikuna (AOR = 4.3, 95% CI = 1.3, 13.6), kinne (AOR = 4.5, 95% CI = 1.4, 14.6), aquaquame (AOR = 9.9, 95% CI = 2.5, 39.88), tirguame (AOR = 6.4, 95% CI = 1.6, 25.6), and among those whose mothers had no formal education [AOR = 3.7, 95% CI: 1.2, 12.8]. In contrast, those adolescents who always washed their hands after a toilet visit had lower odds of undernutrition than their counterparts [AOR = 0.7, 95%CI: 0.5, 0.98]. Conclusion More than three out of five participating male adolescents were undernourished. Thus, to improve the nutritional status of adolescents studying in traditional church schools, extensive health education for these adolescents is essential. Moreover, the establishment of well-resourced traditional religious school, equipped for the provision of an adequate, diversified diet, is important. Developing the habit of handwashing after visiting the toilet and before and after food preparation is also recommended for adolescent students.